(untitled) (American International Journal of Education and Linguistics Research, 2019)
School Based Management Inventories first edition (SBMI-1) was self-developed in 2014 to be a measure of the extent of involvement of stake holders in the educational administrations. The inventories examined factors such as power decentralization (for instance, decision that concerns the school administration do involves the community), provision of facilities (for instance., community assistance in the provision of basic facilities such as classroom buildings, renovations, among others.), monitoring and evaluation of the teaching, learning activities of the school system, recruitment and retrenchment (for instance., On account of necessity, how community recruit new staff to the school as ad hoc staff), and financial obligation in form of periodic expenses and income analysis by the community committee, efficient and effective practice of school based management in determining students’ academic performance in secondary schools. The measure also helps in monitoring school progress and effectiveness.